Composition

By using a composition containing a solvent, a carbonization catalyst generator and a carbonizable organic material in a battery module or battery pack, the problems of abnormal heating, ignition and explosion are solved, and effective isolation of heat and stable storage and operation are achieved.

CN119654184APending Publication Date: 2025-03-18LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380058169.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2023-09-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with the problems of abnormal heating, ignition and explosion in products composed of multiple heating elements, especially in battery modules or battery packs, where the spread of heat may lead to chain ignition or explosion.

Method used

A composition is developed that comprises a solvent, a carbonization catalyst generator and a carbonizable organic material to form carbides that are effectively flame retardant and heat-insulated at high temperatures by controlling the freezing point and boiling point of the solvent.

Benefits of technology

The composition is able to effectively respond to abnormal heat generation, ignition and explosion, prevent heat from spreading, and ensure excellent operability and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263084900000221
    Figure BDA0005263084900000221
  • Figure BDA0005263084900000301
    Figure BDA0005263084900000301
  • Figure BDA0005263084900000302
    Figure BDA0005263084900000302
Patent Text Reader

Abstract

The present specification discloses a composition for use in a product or element that generates heat or has the potential for fire or explosion during the driving, storage and / or maintenance process, thereby being able to effectively respond to heat, fire and explosion. For example, the composition is applied to an article comprising a plurality of products or elements so as to be able to respond to abnormal heat, explosion and fire occurring in any of the elements or products and prevent or minimize the propagation of such heat, explosion and fire to other adjacent elements or products. The composition also exhibits excellent workability and storage stability. The present specification may also provide uses of the composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application has the benefit of priority based on Korean Patent Application Nos. 10-2022-0125266 and 10-2022-0125271, filed on September 30, 2022, and Korean Patent Application No. 10-2023-0041417, filed on March 29, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0002] This specification discloses compositions and uses thereof. Background Art

[0003] Technologies for handling heat generated by products are becoming increasingly important, but handling, maintaining and controlling heat in products composed of multiple heat generating elements (heating elements) is a difficult problem.

[0004] For example, a battery module or battery pack includes a plurality of battery cells or a plurality of battery modules positioned adjacent to each other. Therefore, heat, fire and / or explosion generated by one battery cell or battery module may affect other adjacent components and, in some cases, may cause problems such as chain fire or chain explosion. In such products, it is necessary to prevent heat, explosion or fire generated by one component from affecting other adjacent components. Summary of the invention

[0005] Technical issues

[0006] The present specification discloses a composition and its use. The present specification is intended to disclose such a composition: the composition is applied to a product or component with the possibility of abnormal heating, fire and / or explosion during driving, storage and / or maintenance process, so as to effectively respond to heating, fire and explosion.

[0007] For example, the composition disclosed in this specification is applied to an article comprising a plurality of the products or components, so as to be able to respond to abnormal heating, explosion and / or fire occurring in any one component or product, and prevent or minimize the spread of such heating, explosion and / or fire to other adjacent components or products.

[0008] Furthermore, an object of the present application is to provide such a composition which ensures excellent handleability and storage stability. Furthermore, an object of the present application is to provide the use of such a composition.

[0009] Technical Solution

[0010] Among the physical properties mentioned in this specification, unless otherwise specified, the physical properties in which temperature affects the physical properties are physical properties measured at room temperature.

[0011] In this specification, the term room temperature is a natural temperature without heating or cooling, which means, for example, any temperature within a range of about 10°C to 30°C, for example, a temperature around about 23°C or about 25°C.

[0012] Unless otherwise specified herein, the unit of temperature mentioned herein is °C.

[0013] Among the physical properties mentioned in this specification, unless otherwise specified, when pressure affects the results, the relevant physical properties are physical properties measured under normal pressure.

[0014] In this specification, the term normal pressure is a natural pressure without pressurization or depressurization, wherein generally a degree within a range of about 700 mmHg to 800 mmHg is referred to as normal pressure.

[0015] In the physical properties mentioned in this specification, unless otherwise specified, when humidity affects the result, the relevant physical properties are physical properties measured under humidity of standard state. Humidity of standard state means relative humidity of about 40%, 50%, 60% or 65%.

[0016] This specification discloses a composition. In this specification, the term composition may refer to a mixture of two or more different components. The composition may be a fire extinguishing composition. A fire extinguishing composition is a composition that is capable of responding to abnormal heating, fire and / or explosion occurring in any target.

[0017] The composition may include a solvent. The solvent may be used to reduce heat by heat exchange, etc. when heat generation, fire and / or explosion occurs in a target adjacent to the composition, or to eliminate the flame generated by the fire and / or explosion. Such a solvent may enable the composition to exhibit latent heat as described below, and may also enable the carbonizable organic material as described below to effectively form a carbide at a necessary time point.

[0018] For example, the solvent may be an evaporable solvent. When heat is applied to the solvent due to abnormal heating, fire and / or explosion, the solvent evaporates due to the heat, and the gas generated thereby can reduce heat or can be used to extinguish the flame. In addition, desired latent heat may occur during the evaporation process.

[0019] As the solvent, any non-flammable solvent may be used without particular limitation. For example, a solvent having a freezing point and / or boiling point within a predetermined range may be used as the solvent.

[0020] For example, in order for the solvent to effectively respond to heating, fire and / or explosion, it needs to be in a liquid phase at least at the point in time when heating, fire and explosion occur, and for this purpose, the freezing point of the solvent can be controlled.

[0021] For example, the lower limit of the freezing point of the solvent may be about -5°C, -4°C, -3°C, -2°C, -1°C, or 0°C, and the upper limit thereof may be about 10°C, 9°C, 8°C, 7°C, 6°C, 5°C, 4°C, 3°C, or 2°C. The freezing point may be in the range of less than, equal to, or less than any of the above upper limits; in the range of greater than, equal to, or greater than any of the above lower limits; or in the range of less than, equal to, or less than any of the above upper limits and greater than, equal to, or greater than any of the above lower limits.

[0022] In order for the solvent to effectively respond to exotherm, fire and / or explosion, it may be advantageous for it to be a solvent that can be evaporated by heat generated by at least exotherm, fire and explosion, and for this purpose, the boiling point of the solvent may be controlled.

[0023] The lower limit of the boiling point of the solvent may be about 80° C., 85° C., 90° C., or 95° C., and the upper limit thereof may be about 120° C., 115° C., 110° C., or 105° C. The boiling point may be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0024] As the solvent, an appropriate type may be selected and used without particular limitation as long as it has a freezing point and / or boiling point within the above range and is non-flammable.

[0025] Representative examples of the non-flammable solvent having a freezing point and / or a boiling point within the above range include water, and thus, water may be used as the solvent, but the type of applicable solvent is not limited thereto.

[0026] The lower limit of the ratio of the solvent in the composition can be, for example, about 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, or 80 wt%, and the upper limit can be about 95 wt%, 90 wt%, 85 wt%, 80 wt%, 75 wt%, 70 wt%, 65 wt%, 60 wt%, 55 wt%, 50 wt%, 45 wt%, or 40 wt%. The ratio can be in the range of less than or equal to, or less than any one of the above upper limits; in the range of greater than or equal to, or greater than any one of the above lower limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.

[0027] The composition may include additional ingredients to ensure proper fire extinguishing function. For example, the composition may include a carbonization catalyst generator and a carbonizable organic material. The combination of the above ingredients forms a carbonized organic material at a necessary time point (i.e., when it is necessary to respond to abnormal heating, ignition and / or explosion). The carbide thus formed can block heat transfer. For example, the carbonization catalyst generator can promote the carbonization of the carbonizable organic material and / or the gas generation of the gas generating raw material to be described. The carbonization catalyst generator forms an acid or an acid-based salt or ion at high temperature, and these components can be used to promote the carbonization and gas generation process. In addition, according to the type of the carbonization catalyst generator, the carbide can be given flame retardancy, or a component that exhibits flame retardancy alone can be formed. For example, the carbonization catalyst generator described below forms a material based on phosphoric acid by decomposing at high temperature, etc., and the material can be polymerized to have flame retardancy. Therefore, the carbonization catalyst generator can be included in the composition so that the composition can respond to abnormal heating, ignition and / or explosion.

[0028] The carbonization catalyst generator and the carbonizable organic material as described above need to be applied together with a solvent, wherein a carbonization catalyst generator having a solubility higher than a certain level in a solvent (e.g., water) must be used as the carbonization catalyst generator. That is, the components dispersed in the solvent can more effectively contact each other at a necessary time point and interact with each other to effectively form the desired carbide, etc. In addition, by controlling the solubility of the carbonization catalyst generator in the solvent, agglomeration or phase separation of the components in the composition does not occur, and the above-mentioned carbide formation and / or flame retardant formation can also be more effectively performed. For example, the lower limit of the solubility of the carbonized catalyst generator in the solvent may be about 5g, 10g, 15g, 20g, 25g, 30g, 35g, or 40g, and the upper limit thereof may be about 1000g, 900g, 800g, 700g, 600g, 500g, 400g, 300g, 200g, 100g, 90g, 80g, 70g, 60g, 50g, 40g, or 30g. The solubility may be in a range greater than or equal to, or greater than any of the above lower limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The solubility is the weight (g) of the carbonized catalyst generator that can be dissolved in 100g of a solvent (e.g., water) at 25°C at most. The solubility is measured by the method described in "11. Solubility Evaluation" of the Examples section in this specification.

[0029] The carbonization catalyst generator can be used without particular limitation, as long as it can be decomposed at high temperature to form an acid or an acid-based salt or ion, etc., and has the above solubility. Examples of carbonization catalyst generators include phosphoric acid compounds such as phosphoric acid and phosphates, phosphonate / ester compounds or phosphate / ester compounds. The carbonization catalyst generator can be, for example, ammonium dihydrogen phosphate or diammonium hydrogen phosphate, urea phosphate, guanyl phosphate urea, or ammonium polyphosphate, etc., and one or two or more of the foregoing can be selected and used.

[0030] Taking into account the expected effect, the carbonization catalyst generator can be present in the composition in an appropriate amount. For example, relative to 100 weight portions of the solvent, the lower limit of the weight ratio of the carbonization catalyst generator can be 0.5 weight portion, 1 weight portion, 5 weight portions, 10 weight portions, 11 weight portions, 12 weight portions, 13 weight portions, 14 weight portions, 15 weight portions, 16 weight portions, 17 weight portions, or about 18 weight portions, and its upper limit can be 100 weight portions, 95 weight portions, 90 weight portions, 85 weight portions, 80 weight portions, 75 weight portions, 70 weight portions, 65 weight portions, 60 weight portions, 55 weight portions, 50 weight portions, 45 weight portions, 40 weight portions, 35 weight portions, 30 weight portions, 25 weight portions, 20 weight portions, or about 15 weight portions. The ratio may be in a range of less than or equal to, or less than any one of the above upper limits; in a range of greater than or equal to, or greater than any one of the above lower limits; or in a range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. If the content of the carbonization catalyst generator having excellent solubility in the solvent is too high, the amount of the solvent applicable to the composition is limited, and the evaporation characteristics of the solvent are affected by the carbonization catalyst generator dissolved in the solvent, thereby making it difficult to ensure the desired latent heat, so that the amount of the carbonization catalyst generator may be adjusted in consideration of this issue.

[0031] The composition may comprise a carbonizable organic material as a further component.

[0032] Carbonizable organic materials are organic materials that carbonize to form carbides when exposed to flames or heat at a predetermined temperature. Carbides formed by such organic materials are generally porous, thereby being able to have a heat-insulating function. Therefore, when the composition is exposed to abnormal heating, fire or explosion, the organic material can exhibit a heat-insulating function by forming appropriate carbides. As described above, by adding a specific carbonization catalyst generator and a carbonizable organic material to a solvent, even when a small amount of a carbonizable organic material is applied, a carbide that can effectively respond to abnormal heating, fire and / or explosion can be formed.

[0033] Furthermore, when a gas generating material described below is used together, porous carbide can be formed more efficiently by the action of gas generated by the gas generating material in the process of forming carbide from the organic material. In addition, the carbonization catalyst generating agent allows the carbonizable organic material to form carbide more efficiently.

[0034] As the organic material, any appropriate type can be applied without any particular limitation as long as it is a material that forms carbide when exposed to heat or flame.

[0035] Examples of such organic materials include sugars such as sorbitol or mannitol, polysaccharides such as starch or dextrin (e.g., MC (maleated cyclodextrin) or metal salts of MC, etc.), polyols such as pentaerythritol, dipentaerythritol, tripentaerythritol, or THEIC (tris (hydroxyethyl) isocyanurate), cellulose, BSPPO,

[0036] (bi(4-methoxy-1-phospha-2,6,7-trioxabicyclo[2.2.2]-octan-1-sulfide)phenylp hosphate, lignin (alkali lignin or urea-modified lignin, etc.), melamine compounds such as hydroxymethyl melamine, phenolic resins and / or carbonizable polymers (carbon-forming polymers) such as PA6T (poly-hexa methyleneterephthalamide), but are not limited thereto.

[0037] A material that can be used as the carbonizable organic material is starch. Starch is relatively easy to obtain and can form a suitable carbide when exposed to heat or flame.

[0038] The type of starch can be adjusted so that carbide is effectively formed and the formed carbide effectively exerts the desired fire extinguishing or heat insulating effect.

[0039] For example, as starch, starch containing amylose and amylopectin whose ratio is adjusted to an appropriate level can be used. As known, amylopectin and amylose are types of polysaccharides mainly present in plants, and the starch of the polysaccharide is composed of amylose and amylopectin. Amylose is composed of glucose molecules connected by α (1→4) glycosidic bonds and has a linear chain structure, while amylopectin has a relatively short and highly branched chain. Compared with amylopectin, amylose is relatively easy to crystallize, and amylopectin has a relatively higher solubility in water than amylose.

[0040] By using starch having the above characteristics in which amylose and amylopectin are present at an appropriate ratio, a desired composition can be provided more effectively.

[0041] For example, in a starch containing amylose and amylopectin, the lower limit of the weight ratio of amylopectin relative to 100 parts by weight of amylose may be about 150 parts by weight, 200 parts by weight, 250 parts by weight, or 300 parts by weight, and the upper limit thereof may be about 900 parts by weight, 850 parts by weight, 800 parts by weight, 750 parts by weight, 700 parts by weight, 650 parts by weight, 600 parts by weight, 550 parts by weight, 500 parts by weight, 450 parts by weight, 400 parts by weight, 350 parts by weight, or about 300 parts by weight. The ratio may be in a range of less than or equal to, or less than any one of the above upper limits; in a range of greater than or equal to, or greater than any one of the above lower limits; or in a range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The ratio of amylose to amylopectin may be measured by the method described in "9. Measurement of amylopectin and amylose content" in the Examples section of this specification.

[0042] As starch, starch having a molecular weight (e.g., weight average molecular weight (Mw)) within a predetermined range can be used. For example, the lower limit of the weight average molecular weight of starch can be 200,000 g / mol, 250,000 g / mol, 300,000 g / mol, 350,000 g / mol, 400,000 g / mol, 450,000 g / mol, 500,000 g / mol, 550,000 g / mol, 600,000 g / mol, 650,000 g / mol, 700,000 g / mol, 750,000 g / mol, 800,000 g / mol, 850,000 g / mol, 900,000 g / mol, g / mol, 950,000g / mol, 1,000,000g / mol, 1,500,000g / mol, 2,000,000g / mol, 2,500,000g / mol, 3,000,000g / mol, 3,500,000 g / mol, 4,000,000g / mol, 4,500,000g / mol, 5,000,000g / mol, 5,500,000g / mol, 6,000,000g / mol, 6,500,000g / mol, 7,000,00 The molecular weight of the present invention may be about 10 g / mol, 20 g / mol, 30 g / mol, 40 g / mol, 50 g / mol, or 60 g / mol, and the upper limit thereof may be about 1,000,000,000 g / mol, 900,000,000 g / mol, 10,000,000 g / mol, 20,000,000 g / mol, 30,000,000 g / mol, 40,000,000 g / mol, or 50,000,000 g / mol, and the upper limit thereof may be about 1,000,000,000 g / mol, 900,000,000 g / mol, The molecular weight may be about 800,000,000 / mol, 700,000,000 / mol, 600,000,000 / mol, 500,000,000 / mol, 400,000,000 / mol, 300,000,000 / mol, 200,000,000 / mol, 150,000,000 / mol, 100,000,000 / mol, 90,000,000 / mol, 80,000,000 / mol, 70,000,000 / mol, or 60,000,000 / mol. The molecular weight may be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits.Starch having the above molecular weight (Mw) can more effectively form carbides having desired functions (eg, heat insulation functions) when exposed to heat or flame. The molecular weight can be measured by the method described in "8. Molecular weight measurement" of the Examples section of this specification.

[0043] As the carbonizable organic material (e.g., starch), a carbonizable organic material having a gelatinization viscosity within a certain range can be used. Such gelatinization viscosity is related to the characteristics of the carbonizable organic material when it is present in a solvent, wherein by controlling the gelatinization viscosity, carbonization can be formed more efficiently. The lower limit of the gelatinization viscosity of the carbonizable organic material (e.g., starch) may be about 150, 200, 250, 300, 350, 400, 450, 500, 550, 650, 700, 750, 800, 850, 900, 950, or 1,000, and the upper limit thereof may be about 5,000, 4,500, 4,000, 3,500, 3,000, 2,500, 2,000, 1,500, 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, or 300. The gelatinization viscosity may be in a range of less than or equal to, or less than any of the above upper limits; in a range of greater than or equal to, or greater than any of the above lower limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The gelatinization viscosity can be measured by the method described in "12. Evaluation of gelatinization viscosity" in the Examples section of this specification, wherein the unit is BU (Brabender unit).

[0044] The lower limit of the weight ratio of the carbonizable organic material relative to 100 parts by weight of the solvent may be about 0.01 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 9.5 parts by weight, or about 10 parts by weight, and the upper limit thereof may be about 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 29 parts by weight, 28 parts by weight, 27 parts by weight, 26 parts by weight, 25 parts by weight, 24 parts by weight, 23 parts by weight, 22 parts by weight, 21 parts by weight, 20 parts by weight, 19 parts by weight, 18 parts by weight, 17 parts by weight, 16 parts by weight, 15 parts by weight, 14 parts by weight, 13 parts by weight, 12 parts by weight, 11 parts by weight, 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, or about 5 parts by weight. The ratio may be within a range of less than or equal to, or less than any of the above upper limits; within a range of greater than or equal to, or greater than any of the above lower limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The carbonizable organic material contained in such a ratio can effectively form carbides in the composition when necessary, and can ensure that the composition as a whole has excellent operability and storage stability.

[0045] When the composition includes a carbonizable organic material, the weight ratio (M / O) of the above-mentioned carbonization catalyst generator (M) to the carbonizable organic material (O) can be adjusted. For example, the lower limit of the ratio M / O can be about 0.5, 1, 1.5, 2, 2.5, or 3, and the upper limit thereof can be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3.5, 3, or 2.5. The ratio can be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits. The carbonizable organic material contained in such a ratio can play an effective inhibitory effect on heat or flame and a formation effect of porous carbides in the composition when necessary, and can ensure that the composition has excellent operability and storage stability as a whole.

[0046] The composition may also include a gas generating material as an optional additional ingredient. A gas generating material that may be included in the composition is a material that generates gas when exposed to heat or flame. The gas thus generated may serve to directly extinguish the heat or flame, and in the process of forming the carbide by the carbonizable organic material, may also serve to make the carbide more porous.

[0047] The type of gas generated by the gas generating material is not particularly limited as long as it is a non-combustible gas, and may be, for example, nitrogen, carbon dioxide, and / or water vapor.

[0048] Various materials for generating gas are known. For example, materials for generating nitrogen can be exemplified by melamine, guanidine, urea, melamine pyrophosphate, dicyandiamide, guanyl phosphate urea, and glycine, etc.; materials for generating carbon dioxide can be exemplified by potassium bicarbonate, sodium bicarbonate, calcium bicarbonate, and magnesium bicarbonate, etc.; and materials for generating water vapor can be exemplified by calcium hydroxide, magnesium hydroxide, and aluminum hydroxide, etc., but the materials suitable for the present application are not limited thereto.

[0049] As the gas generating material, one or a mixture of two or more selected from the above-mentioned types may be used.

[0050] In order to produce a suitable effect, as the gas generating material, a material that generates nitrogen can be used, for example, melamine, guanidine, urea, melamine pyrophosphate and / or guanyl phosphate urea, etc. In particular, in the process of carbonizing organic materials to form carbides, these materials are advantageous in that they more effectively exert a foaming effect on carbides, thereby effectively forming the desired porous carbides.

[0051] When included, the lower limit of the weight ratio of the gas generating material relative to 100 parts by weight of the solvent can be about 0.01 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, or 40 parts by weight, and the upper limit thereof can be about 100 parts by weight, 95 parts by weight, 90 parts by weight, 85 parts by weight, 80 parts by weight, 75 parts by weight, 70 parts by weight, 65 parts by weight, 60 parts by weight, 55 parts by weight, 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 25 parts by weight, 20 parts by weight, 15 parts by weight, 10 parts by weight, or 8 parts by weight. The ratio may be within a range of less than or equal to, or less than any one of the above upper limits; within a range of greater than or equal to, or greater than any one of the above lower limits; or within a range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The gas generating material included in such a ratio can exert an effective suppression effect on heat or flame and a porous carbide formation effect in the composition when necessary, and can ensure that the composition as a whole has excellent operability and storage stability.

[0052] When the composition includes a gas generating material, the weight ratio (M / G) of the above-mentioned carbonization catalyst generating agent (M) and the gas generating material (G) can be adjusted. For example, the lower limit of the ratio M / G can be about 0.5, 1, 1.5, 2, 2.5, or 3, and the upper limit thereof can be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, or 4. The ratio can be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The gas generating material included in such a ratio can play an effective inhibitory effect on heat or flame and a formation effect of porous carbide in the composition when necessary, and can ensure that the composition has excellent operability and storage stability as a whole.

[0053] The composition may comprise water-absorbing polymers as an optional further ingredient.

[0054] The water-absorbing polymer is a polymer having the property of being able to absorb water.

[0055] In one example, the water-absorbing polymer may be a so-called hydrogel polymer or hydrogel, which is generally defined as a cross-linked hydrophilic polymer. Such polymers are also referred to as SAP (Super Adsorbent Polymer).

[0056] The water-absorbent polymer is a material that can absorb water several tens to several thousand times its own weight. Such a material enables the composition of the present application to exist in a gel state as a whole, thereby playing a role in ensuring operability and storage stability.

[0057] The type of applicable water-absorbing polymer is not particularly limited, and any polymer generally usable as SAP may be used without limitation.

[0058] Generally, a polyacrylate-based vinyl polymer is used as the above material. Here, the polyacrylate-based polymer is a polymer made from an acrylate-based monomer, and if necessary, other comonomers may be used to form the polymer.

[0059] The water absorption properties can be adjusted so that the water-absorbing polymer exhibits properties suitable for the use in the present application.

[0060] For example, according to EDANA (European Disposables and Nonwovens Association) method WSP 241.3, the lower limit of the centrifuge retention capacity (CRC) of the water-absorbent polymer can be about 12 g / g, 13 g / g, 14 g / g, 15 g / g, 16 g / g, 17 g / g, 18 g / g, 19 g / g, 20 g / g, 21 g / g, 22 g / g, 23 g / g, 24 g / g, 25 g / g, 26 g / g, 27 g / g, 28 g / g, 29 g / g, 30 g / g, 31 g / g, 32 g / g, or 33 g / g, and the upper limit thereof can be about 60 g / g, 55 g / g, 50 g / g, 45 g / g, 40 g / g, or 35 g / g. The centrifuge retention capacity (CRC) may be within a range of less than or equal to, or less than any of the above upper limits; within a range of greater than or equal to, or greater than any of the above lower limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The centrifuge retention capacity (CRC) may be evaluated by the method described in "6. CRC (centrifuge retention capacity)" in the Examples section of this specification.

[0061] For example, according to EDANA (European Disposables and Nonwovens Association) method WSP 242.3, the lower limit of the absorption under pressure (AUP) of the water-absorbent polymer at 0.3 psi can be about 4 g / g, 6 g / g, 8 g / g, 10 g / g, 12 g / g, 14 g / g, 16 g / g, 18 g / g, 20 g / g, 22 g / g, 24 g / g, 26 g / g, 27 g / g, or 28 g / g, and the upper limit thereof can also be about 40 g / g, 38 g / g, 36 g / g, 34 g / g, 32 g / g, or 30 g / g. The absorption under pressure (AUP) can be in the range of less than or equal to, or less than any of the above upper limits; in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The absorbency under pressure (AUP) can be evaluated by the method described in "7. AUP (Absorption Under Pressure)" of the Example section in the present specification.

[0062] The water-absorbent polymer having the above absorbency may be combined with other components of the composition of the present application to exhibit desired characteristics.

[0063] In one example, the water-absorbing polymer may be a particulate polymer. The weight-based size distribution of the particulate water-absorbing polymer may be controlled to ensure the desired viscosity characteristics and fire extinguishing function by applying the water-absorbing polymer. In the present specification, the term weight-based size distribution of water-absorbent polymer is a size distribution measured according to the description of "13. Weight-based size distribution of water-absorbent polymer" in the Example section of the present specification, which means a size distribution in which a sample of the particulate water-absorbent polymer is divided into the following particle fractions: a particle fraction having a size less than 150 μm (hereinafter, may be referred to as "A particle fraction"), a particle fraction in the range of 150 μm to 300 μm (hereinafter, may be referred to as "B particle fraction"), a particle fraction in the range of 300 μm to 600 μm (hereinafter, may be referred to as "C particle fraction"), a particle fraction in the range of 600 μm to 850 μm (hereinafter, may be referred to as "D particle fraction"), and a particle fraction exceeding 850 μm (hereinafter, may be referred to as "E particle fraction"), and the weight of each particle fraction is expressed as a percentage relative to the weight of the entire particulate water-absorbent polymer sample (the weight ratio of each particle fraction). The weight-based size distribution can be obtained according to the EDANA method WSP 220.3 standard as described in "17. Weight-based size distribution of water-absorbing polymers" in the above Examples section.

[0064] In the weight-based size distribution, the maximum weight size of the particulate water-absorbent polymer may be in the range of 150 μm to 850 μm. Here, the maximum weight size is the size of the particle size showing the highest weight ratio among the weight ratio of the A particle size, the weight ratio of the B particle size, the weight ratio of the C particle size, the weight ratio of the D particle size, and the weight ratio of the E particle size. That is, the case where the maximum weight size is in the range of 150 μm to 850 μm means that the weight ratio of the particulate water-absorbent polymer belonging to any one of the B particle size, the C particle size, and the D particle size, or two or more, shows the maximum value. Since the weight ratios of the two particle sizes are the same, and their weight ratios may also represent the highest value among the weight ratios of all the particle sizes, the particle size having the maximum weight size may also be one, two, or more. In one example, the particle size having the maximum weight size may be the C particle size among the B particle size, the C particle size, and the D particle size. Therefore, the maximum weight size in the weight-based size distribution may also be in the range of 300 μm to 600 μm.

[0065] The weight ratio of the particle fraction representing the maximum weight size in the weight-based size distribution of the particulate water-absorbent polymer (i.e., the weight ratio of the water-absorbent polymer belonging to the maximum weight size in the weight-based size distribution) may have a lower limit of about 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, or 74 wt%, and an upper limit thereof may be about 95 wt%, 90 wt%, 85 wt%, 80 wt%, 79 wt%, 78 wt%, 77 wt%, 76 wt%, or 75 wt%. The weight ratio may be in the range of greater than or equal to, or greater than any of the above lower limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0066] If the maximum weight size is too small and / or the weight ratio of the particle size representing the maximum weight size is too small, the composition will not properly form a desired gel, thereby possibly reducing handling and storage characteristics, or it may fail to exert a fire extinguishing function, so that an appropriate particulate water-absorbent polymer may be selected in consideration of this.

[0067] When included, the weight ratio of the water-absorbent polymer relative to 100 parts by weight of the solvent may have a lower limit of about 0.01 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, or 9 parts by weight, and an upper limit thereof may be about 50 parts by weight, 45 parts by weight, 40 parts by weight, 35 parts by weight, 30 parts by weight, 29 parts by weight, 28 parts by weight, 27 parts by weight, 26 parts by weight, 25 parts by weight, 24 parts by weight, 23 parts by weight, 22 parts by weight, 21 parts by weight, 20 parts by weight, 19 parts by weight, 18 parts by weight, 17 parts by weight, 16 parts by weight, 15 parts by weight, 14 parts by weight, 13 parts by weight, 12 parts by weight, 11 parts by weight, 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, or 2 parts by weight. The ratio can be within a range of less than or equal to, or less than any of the above upper limits; within a range of greater than or equal to, or greater than any of the above lower limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.

[0068] The composition includes the above ingredients, and may include additional ingredients if necessary.

[0069] For example, the composition may also include a freezing point regulator. As mentioned above, in order for the composition to perform a fire extinguishing function, it is advantageous for the solvent, etc. to be in a liquid phase at a time point when the heating, ignition and / or explosion that must be controlled occurs. However, depending on the application, the environment in which the composition is placed may be at a temperature lower than the freezing point of the composition or the solvent, and in this case, there is a high probability that the composition does not exist in a liquid phase. Therefore, in this case, it is necessary to adjust the freezing point of the composition by adding an appropriate freezing point regulator.

[0070] The type of freezing point adjuster suitable for use in this process is not particularly limited, and additives known to be capable of controlling the freezing point of a solvent or a composition by a so-called freezing point depression phenomenon may be used.

[0071] For example, alcohols may be used as freezing point modifiers.

[0072] For example, as alcohol, an alcohol having a boiling point within a predetermined range can be used. For example, the lower limit of the boiling point of the alcohol may be about 150° C., 170° C., or 190° C., and the upper limit thereof may be about 300° C., 280° C., 260° C., 240° C., 220° C., or 200° C. The boiling point may be in a range lower than or equal to, or lower than any of the above upper limits; in a range higher than or equal to, or higher than any of the above lower limits; or in a range lower than or equal to, or lower than any of the above upper limits and higher than or equal to, or higher than any of the above lower limits.

[0073] For example, as alcohol, alcohol with a molar mass within a predetermined range can be used. For example, the lower limit of the molar mass of alcohol can be about 20g / mol, 30g / mol, 40g / mol, 50g / mol, 60g / mol, 70g / mol, 80g / mol, or 90g / mol, and the upper limit can be about 300g / mol, 280g / mol, 260g / mol, 240g / mol, 220g / mol, 200g / mol, 180g / mol, 160g / mol, 140g / mol, 120g / mol, 100g / mol, 90g / mol, 80g / mol, or 70g / mol. The molar mass can be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.

[0074] The type of alcohol that can be used is not particularly limited, and for example, a polyhydric alcohol such as ethylene glycol or glycerin can be used.

[0075] If applicable, alcohol can be present so that the concentration calculated based on solvent is within a predetermined range. The concentration at this time is a weight molar concentration, which can be obtained specifically by dividing the mole number of alcohol applied to the composition by the weight (unit: kg) of the solvent. In an example, the lower limit of the weight molar concentration can be about 2, 4, 6, 8, 10, 12, 14 or 16, and its upper limit can be about 50, 48, 46, 44, 42, 40, 38, 36, 34, 32, 30, 28, 26, 24, 22 or 20. The weight molar concentration can be less than or equal to or less than the scope of any one of the above-mentioned upper limits; in the scope of greater than or equal to or greater than any one of the above-mentioned lower limits; or in the scope of less than or equal to or less than any one of the above-mentioned upper limits and greater than or equal to or greater than any one of the above-mentioned lower limits. However, the weight molar concentration can be adjusted considering the desired freezing point range.

[0076] By combining the above components, such compositions can exhibit unique physical properties.

[0077] For example, the composition can exhibit a fully controlled freezing point. For example, the lower limit of the freezing point of the composition can be about -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, or -10°C, and the upper limit can be about 10°C, 8°C, 6°C, 4°C, 2°C, 0°C, -5°C, -10°C, -15°C, -20°C, -25°C, -30°C, -35°C, or -40°C. The freezing point can be in a range of less than or equal to, or less than any of the above upper limits; in a range of greater than or equal to, or greater than any of the above lower limits; or in a range of less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits. Such freezing points can be measured by the methods described in the Examples section.

[0078] The composition may have a controlled viscosity and / or thixotropic index.

[0079] For example, the lower limit of the viscosity of the composition may be 30,000 cP, 40,000 cP, 50,000 cP, 60,000 cP, 70,000 cP, 80,000 cP, 90,000 cP, 100,000 cP, 110,000 cP, 120,000 cP, 130,000 cP, 140,000 cP, 150,000 cP, or 155,000 cP. Right, and its upper limit can be 600,000cP, 550,000cP, 500,000cP, 450,000cP, 400,000cP, 350,000cP, 300,000cP, 250,000cP, 200,000cP, 150,000cP, 100,000cP, 90,000cP, 80,000cP or 70,000cP or so. The viscosity can be less than or equal to, or less than any one of the above upper limits; in a range greater than or equal to, or greater than any one of the above lower limits; or in a range less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits. Such viscosity is a value measured at room temperature (about 25° C.) and a rotation speed of 0.5 rpm, and the specific measurement method is described in the Examples section.

[0080] For example, the lower limit of the thixotropic index of the composition can be about 2, 4, 6, 8, 10, or 10.5, and the upper limit thereof can be about 20, 18, 16, 14, 12, 10, 8, or 6. The thixotropic index can be in a range of less than or equal to, or less than any one of the above upper limits; in a range of greater than or equal to, or greater than any one of the above lower limits; or in a range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The thixotropic index is a value obtained by dividing the viscosity measured at room temperature (about 25° C.) and 0.5 rpm by the viscosity measured at room temperature (about 25° C.) and 5 rpm, and the specific measurement method is described in the Examples section.

[0081] A composition having such a viscosity and / or thixotropic index may exhibit excellent workability, storage stability, and the like.

[0082] The composition may exhibit certain latent heat properties. Latent heat is generally defined as the amount of heat required for any material to cause a change of state (phase change) without any temperature change. However, the latent heat of a composition as referred to herein does not necessarily mean only the property that occurs when the composition causes a change of state as a whole. Latent heat can be generated in the process of changing the state of at least a portion of the composition or a component contained in the composition.

[0083] In this specification, the case where the composition exhibits latent heat means that the composition shows an endothermic peak in a DSC (differential scanning calorimeter) analysis performed in the manner described in "5. Measurement of latent heat" of the Examples section in this specification. The phase change process in which the composition exhibits latent heat may be an isothermal process, but does not necessarily have to be an isothermal process. By having an appropriate level of latent heat, the composition can be applied to heat-generating products to control heat while keeping the temperature of the product uniform, and the influence of abnormal heating, explosion and / or fire occurring in one product on other adjacent products can be minimized or prevented.

[0084] The lower limit of the latent heat exhibited by the composition may be, for example, about 500 J / g, 550 J / g, 600 J / g, 650 J / g, 700 J / g, 750 J / g, 800 J / g, 850 J / g, 900 J / g, 950 J / g, 1000 J / g, 1100 J / g, 1200 J / g, or 1300 J / g, and the upper limit thereof may be 5000 J / g, 4800 J / g, 4600 J / g. The latent heat may be in the range of greater than or equal to, or greater than any one of the above lower limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The latent heat may be measured by the method described in "5. Latent Heat Measurement" of the Examples section of this specification.

[0085] The lower limit of the range of the starting temperature at which the composition begins to express latent heat may be, for example, about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C, and the upper limit thereof may be about 200°C, 180°C, 160°C, 140°C, 120°C, 100°C, 90°C, or 80°C. The starting temperature may be determined in the range of being higher than or equal to, or higher than any of the above lower limits while being lower than or equal to, or lower than any of the above upper limits. The starting temperature means the temperature of the left starting point of the endothermic peak interval of the DSC analysis performed according to the method described in "5. Measurement of latent heat" of the Example section in this specification.

[0086] The lower limit of the temperature interval representing the latent heat of the composition may be, for example, about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, or 180°C, and the upper limit thereof may be about 300°C, 280°C, 260°C, 240°C, 220°C, 200°C, 180°C, or 160°C. The temperature interval range may be determined within a range higher than or equal to, or higher than any of the above lower limits while lower than or equal to, or lower than any of the above upper limits. The temperature interval is a value obtained by subtracting the temperature of the left starting point from the temperature of the right starting point in the endothermic peak interval of the DSC analysis performed according to the method described in "5. Measurement of latent heat" of the Example section in this specification.

[0087] Through the above characteristics, the composition can be applied to various applications to effectively respond to heat generation, fire and / or explosion occurring in the corresponding applications.

[0088] The freezing point, viscosity, thixotropic index and latent heat characteristics of the composition as described above can be ensured by the combination of the components of each composition as described above.

[0089] Furthermore, the composition may further contain various types of known additives as long as the above-mentioned physical properties are not impaired.

[0090] The present application also relates to a fire extinguishing assembly manufactured using the composition. Considering the storage ease and operation stability of the composition, the fire extinguishing assembly can be manufactured by loading the composition into a suitable housing.

[0091] Thus, the fire extinguishing assembly may include: a housing; and the composition present in the housing.

[0092] The type of housing used to manufacture the fire extinguishing assembly is not particularly limited, and can be used if the housing can appropriately store the composition. The composition contains a volatile component such as a solvent, so that in one example, a housing having a so-called WVTR (Water Vapor Transmission Rate) within a predetermined range can be used as the housing.

[0093] For example, the upper limit of the so-called WVTR (water vapor transmission rate) in the above housing may be 0.5 g / m 2 Day, 0.45g / m 2 Day, 0.4g / m 2 Day, 0.35g / m 2 Day, 0.3g / m 2 Day, 0.25g / m 2Day, 0.2g / m 2 Day, 0.15g / m 2 ·day, or 0.1g / m 2 · days, and its lower limit can be 0g / m 2 Day, 0.1g / m 2 Day, 0.2g / m 2 Day, 0.3g / m 2 Day, 0.4g / m 2 ·day, or 0.5g / m 2 · days. The WVTR may be in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. The WVTR may be evaluated according to the method described in "10. WVTR (water vapor transmission rate) evaluation" in the Examples section of this specification.

[0094] Such a housing can be manufactured using various known materials. For example, the housing can be constructed using appropriate inorganic films and / or organic films, or can be constructed by laminating them.

[0095] Here, applicable organic films can be exemplified as cellulose-based polymer films; COP (cyclic olefin copolymer) films; acrylic polymer films; polyolefin films; PVA (polyvinyl alcohol) films; PES (polyethersulfone) films; PEEK (polyetheretherketone) films; PPS (polyphenylsulfone) films; PEI (polyetherimide) films; PEN (polyethylene naphthalate) films; polyester films; PI (polyimide) films; polysulfone (PSF) films; and / or PAR (polyarylate) films; and the like.

[0096] Here, the applicable inorganic film can be exemplified as a metal film, a metal oxide film, a metal nitride film or a metal oxynitride film, and the like. For example, a metal film, a metal oxide film, a metal nitride film or a metal oxynitride film containing one or more selected from In, Sn, Pb, Au, Cu, Ag, Zr, Hf, Zn, Al, Si, La, Ti and Ni can be used.

[0097] By selecting appropriate types of these films and combining them as required, a desired type of housing can be provided.

[0098] Here, the form of the housing or the fire extinguishing assembly is determined according to the intended use, and is not particularly limited.

[0099] For example, as described below, when the fire extinguishing assembly is applied to a battery module and applied between a plurality of battery cells included in the module, the fire extinguishing assembly may be manufactured by manufacturing a housing having a shape identical to or similar to a battery cell and then inserting it between the battery cells.

[0100] The specification also discloses electronic equipment or devices using the composition or fire extinguishing assembly.

[0101] The type of electronic equipment or device is not particularly limited. For example, the composition or fire extinguishing assembly can be applied to equipment or devices in which there is a risk of abnormal heating, fire and / or explosion during driving, maintenance and / or storage and the related abnormal phenomena must be controlled.

[0102] Examples of the above devices or apparatuses include batteries. In particular, in a battery module constructed using a plurality of battery cells, it is important to prevent abnormal heating, fire, and / or explosion occurring in one battery cell from propagating to other adjacent battery cells.

[0103] Therefore, the present application may relate to a battery module including the composition or fire extinguishing assembly.

[0104] Such a battery module may basically include: a plurality of battery cells; and the combination or fire extinguishing assembly disposed between the battery cells.

[0105] If the composition or fire extinguishing assembly is applied, the specific configuration of the battery module (e.g., the type of battery cell, etc.) is not particularly limited, and known materials can be applied. For example, known pouch-shaped battery cells, rectangular battery cells, or cylindrical battery cells can be used as battery cells.

[0106] The manufacturing method of the battery module is not particularly limited, and for example, as described above, a method may be used in which the fire extinguishing assembly is manufactured as a battery cell and then placed at a desired position during the manufacturing process of the battery module.

[0107] Beneficial Effects

[0108] This specification discloses a product or element that is applied to generate heat or has a possibility of catching fire or exploding during a driving, storage and / or maintenance process, so that a composition that can effectively respond to heat, catching fire and exploding can be used. For example, the composition is applied to an article comprising a plurality of products or elements, so that it can respond to abnormal heating, explosion and catching fire that occur in any element or product, and prevent or minimize the spread of such heating, explosion and catching fire to other adjacent elements or products. The composition also shows excellent operability and storage stability. This specification can also provide the purposes of the composition. DETAILED DESCRIPTION

[0109] Hereinafter, the composition disclosed herein will be described in more detail with reference to Examples and Comparative Examples, but the scope of the composition is not limited by the following Examples.

[0110] 1. Convection test

[0111] Composition is loaded in the aluminum dish that bottom thickness is about 0.2mm.Carry out load so that the thickness of composition is about 3mm.Aluminum dish is placed on temperature sensor (k type thermocouple), and vertically applies flame towards composition at the height of about 1 inch of composition loaded on dish.Use butane gas and blowtorch to apply flame.Measure temperature with temperature sensor while applying flame about 3 minutes, and it is evaluated according to the following standard.

[0112] <Evaluation Criteria>

[0113] PASS: When the measured temperature of the temperature sensor remains below 200°C

[0114] NG: When the temperature sensor measures a temperature of 200°C or above, or the aluminum plate is observed to be melted

[0115] 2. Formation of carbides (porous carbides, foams)

[0116] After the convection test, the position where the composition was loaded was observed and evaluated according to the following criteria.

[0117] <Evaluation Criteria>

[0118] PASS: When the aluminum disk is not damaged and carbides are confirmed at the location of the composition

[0119] NG: When the aluminum disc is damaged or determined to have no carbide

[0120] 3. Chain fire test

[0121] The rectangular batteries are arranged side by side at intervals of about 3 mm, and an assembly (fire extinguishing assembly) containing the composition is placed therebetween. As a rectangular battery, a product of CATL (120Ah, 3.2V, size = thickness × width × width = 48 × 174 × 165) is used, and it is applied to the test at 100% charge state. In the above arrangement, according to the SAE J2464:2009 standard, a battery fire is initiated in one rectangular battery, and a chain fire in another battery cell is checked. The battery fire is caused by piercing a nail with a diameter of about 5 mm into the rectangular battery at a speed of 25 mm / second (nail penetration method).

[0122] <Evaluation Criteria>

[0123] PASS: When no fire occurs in any battery cell other than the one pierced by the nail

[0124] NG: When a fire occurs in a battery cell other than the battery cell pierced by the nail

[0125] 4. Storage stability evaluation

[0126] The fire extinguishing assembly was stored in an oven at a temperature of about 35° C. for 1,000 hours, and the weight change before and after storage in the oven was measured. When the weight change before and after storage was 1% or more, it was evaluated as NG, and when the weight change was less than 1% or there was no weight change, it was evaluated as PASS.

[0127] 5. Measurement of latent heat

[0128] Latent heat is evaluated in the following manner. Each composition of an embodiment or a comparative example is collected in an amount of about 4 mg or so and loaded into a measuring device. As a measuring device, a DSC (differential scanning calorimeter) device (TA Instruments, Q200 type) is used. When evaluating latent heat, the temperature interval is set to 25°C to 300°C. While the temperature is raised from 25°C to 300°C at a rate of about 10°C / minute, the endothermic peak is measured. The left starting point and the right starting point of the endothermic peak interval are designated as the starting point and end point of endothermic absorption, and the latent heat (unit: J / g) is calculated by integrating the relevant interval.

[0129] 6.CRC (centrifugal retention capacity)

[0130] CRC was measured according to EDANA WSP 241.3. About 0.2 g (W0) of water-absorbent polymer was placed in a nonwoven encapsulant, sealed, and then immersed in a physiological saline solution at room temperature. As the physiological saline solution, a 0.9 wt % NaCl aqueous solution was used. This state was maintained for about 30 minutes, and water was removed from the encapsulant using a centrifuge at 250 G for 3 minutes, and then the mass of the encapsulant was measured (g, W2).

[0131] The same operation was performed on the same nonwoven wrapper without any water-absorbing polymer, and the mass (g, W1) was measured.

[0132] CRC(g / g) is calculated by substituting the measurement result into the following equation A.

[0133] The evaluation was performed under constant temperature and humidity conditions (23±1° C., relative humidity: 50±10%).

[0134] [Equation A]

[0135] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0136] 7.AUP (Absorption Percentage Under Pressure)

[0137] AUP was measured according to EDANA method WSP 242.3. A 400 mesh stainless steel wire mesh was mounted on the bottom of a plastic cylinder with an inner diameter of about 60 mm, and 0.0 g (W0) (0.90 g) of water-absorbing polymer was evenly sprayed on the wire mesh, and then a piston capable of evenly imparting a 0.3 psi load was mounted thereon. The piston was slightly smaller than the outer diameter of 60 mm, had no gap with the inner wall of the cylinder, and was mounted so that it could move up and down. The weight of the device was measured (g, W3).

[0138] A glass filter having a diameter and thickness of 90 mm and 5 mm, respectively, was placed in a culture dish having a diameter of 150 mm, and a physiological saline solution was added so that it was at the same level as the upper surface of the glass filter. As the physiological saline solution, a NaCl aqueous solution having a concentration of 0.9 wt % was used. A piece of filter paper having a diameter of 90 mm was placed thereon. A measuring device was placed on the filter paper and the physiological saline solution was absorbed for 1 hour under a load of 0.3 psi. Thereafter, the measuring device was raised and its weight (g, W4) was measured.

[0139] AUP (g / g) was estimated by substituting the obtained value into the following equation B.

[0140] The evaluation was performed under constant temperature and humidity conditions (23±1° C., relative humidity: 50±10%).

[0141] [Equation B]

[0142] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0143] 8. Molecular weight measurement

[0144] The molecular weight of starch was evaluated in the following manner.

[0145] (1) Preparation of mobile phase

[0146] Mobile phase A was prepared by filtering 1000 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 using a solvent purification system (Millipore Millisolve Kit, MilliporeSigma).

[0147] (2) Preparation of sample solution

[0148] A sample intended to be measured was collected in an amount of 25 mg and mixed with 5 mL of a 150 mM NaNO 3 aqueous solution containing 0.02 wt % NaN 3 , and then a sample solution was prepared by heating the mixture at 80° C. for 20 hours and then filtering it with a 0.4 μm nylon syringe filter.

[0149] (3) GPC (Gel Permeation Chromatography) / MALS (Multi-Anglue Light Scattering Detection) Conditions The molecular weight was evaluated using the sample solution and mobile phase A in the following manner.

[0150] Measuring instrument: Agilent GPC (Agilent 1200 series, USA)

[0151] Stationary phase: connected to Shodex OH-Pak 804 column and Shodex OH-Pak 80 column Mobile phase: A; 0.02% NaN3, 150mM NaNO3 aqueous solution = 100 (volume / volume%)

[0152] Flow rate: 0.4mL / min

[0153] Stationary phase temperature: 25°C

[0154] Injection volume: 100 μl (0.45 μm filtered)

[0155] Analysis time: 120 minutes

[0156] 9. Measurement of Amylopectin and Amylose Content

[0157] The amylopectin and amylose contents in starch were evaluated according to the method described in the paper (Potato Research 31 (1988) 241-246).

[0158] First, the sample was prepared by dissolving about 5 mg of starch in about 1 mL of sterile water (step 1) and heating to 95°C in a constant temperature water bath for about 15 minutes (step 2).

[0159] Subsequently, about 20 μl of the sample was placed in a cuvette (step 3), and about 980 μl of the iodine solution was added thereto and mixed (step 4).

[0160] Subsequently, the absorbance of the sample mixed with the iodine solution at wavelengths of 525 nm and 700 nm was measured and recorded, respectively (step 5). The absorbance was measured using the OPTIZEN POP model of KLAB.

[0161] About 20 μl of water is placed in another cuvette, 980 μl of iodine solution is added thereto, and mixed (step 6). For the solution of step 6, the absorbance at wavelengths of 525 nm and 700 nm is measured and recorded in the same manner as in step 5, respectively (step 7).

[0162] The absorbance obtained in step 7 is subtracted from the absorbance obtained in step 5, and the ratio (%) of amylose is determined according to the following equation C (step 8).

[0163] [Equation C]

[0164]

[0165] In equation C, PA is the ratio of amylose (%), OD is 700 is the value obtained by subtracting the absorbance at a wavelength of 700 nm measured in step 7 from the absorbance at a wavelength of 700 nm measured in step 5, and OD 525 is a value obtained by subtracting the absorbance at a wavelength of 525 nm measured in step 7 from the absorbance at a wavelength of 525 nm measured in step 5.

[0166] 10.WVTR (water vapor transmission rate) evaluation

[0167] The WVTR (water vapor transmission rate) of the housing shell of the fire extinguishing assembly was evaluated according to ASTM F1249 standard at 38°C and 100% relative humidity.

[0168] 11. Solubility Assessment

[0169] The solubility of the materials was evaluated based on the ASTM E1148-02 standard. According to the above standard, the solubility was determined by evaluating the amount that dissolved at most in 100 g of water at room temperature (about 25°C).

[0170] 12. Evaluation of gelatinization viscosity

[0171] The gelatinization viscosity of starch was evaluated using an Amylograph-E (brabender) device. About 58 g of starch was dissolved in 450 mL of distilled water. The following process was performed: the temperature of the distilled water in which starch was dissolved was raised from 35°C to 95°C at a rate of 1.5°C / min, the temperature of 95°C was maintained for 15 minutes, and then the temperature was reduced from 95°C to 50°C at a rate of 1.5°C / min. In the above process, the peak that appears when the swelling structure of starch collapses is determined, and the viscosity value of the peak is regarded as the gelatinization viscosity of starch.

[0172] 13. Weight-based size distribution of water-absorbent polymers

[0173] The weight-based size distribution of water-absorbent polymers is measured according to EDANA WSP 220.3. According to the above standard, a stainless steel sieve (diameter: about 200 mm) with a hole size of 150 μm, 300 μm, 600 μm and 850 μm is used to obtain a weight-based size distribution. Using the standard and sieve, the water-absorbent polymer sample is classified based on the particle size, and the weight of the corresponding classified particles is expressed as a percentage. Specifically, the sample is divided into a particle size less than 150 μm, a particle size in the range of 150 μm to 300 μm, a particle size in the range of 300 μm to 600 μm, a particle size in the range of 600 μm to 850 μm, and a particle size greater than 850 μm, and the percentage relative to the weight of the entire sample is determined by measuring the weight of each particle size.

[0174] Example 1.

[0175] Preparation of fire extinguishing composition

[0176] Water (tap water) (W), melamine (M), ammonium dihydrogen phosphate (N) (NH4H2PO4) and starch (S) are mixed in a weight ratio of 78:6:9.5:4 (W:M:N:S) to prepare a mixture. The mixing is performed at room temperature (about 25°C) under a mixing condition of 300rpm for about 60 minutes. As starch, corn starch is used. The weight average molecular weight of the starch is about 51,000,000 g / mol, the weight ratio of amylose to amylopectin (amylose: amylopectin) is about 25:75, and the gelatinization viscosity is about 260 BU (Brabender unit). The solubility of ammonium dihydrogen phosphate (N) (NH4H2PO4) in water at 25°C is about 29 g.

[0177] Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25° C.) under a mixing condition of 500 rpm for about 2 hours.

[0178] Mixing is performed so that the weight ratio of water to water-absorbent polymer (SAP) in the mixture (water: SAP) is about 78:2.5. As the water-absorbent polymer, LG Chemical's GS-803ND product is used. The CRC (centrifuge retention capacity) of the water-absorbent polymer is about 33.5 g / g, and the AUP (absorption rate under pressure) is about 28.1 g / g. In addition, in the size distribution based on weight, the ratio of the particle size less than 150 μm is about 1.5 weight%, the ratio of the particle size in the range of 150 μm to 300 μm is 20.5 weight%, the ratio of the particle size in the range of 300 μm to 600 μm is 74.6 weight%, the ratio of the particle size in the range of 600 μm to 850 μm is 3.4 weight%, and the ratio of the particle size greater than 850 μm is 0 weight%. Therefore, in the weight-based size distribution of the water-absorbent polymer, the maximum weight size was 300 μm to 600 μm, and the weight ratio of the water-absorbent polymer belonging to the maximum weight size was 74.6 wt %.

[0179] Manufacture of fire extinguishing assemblies

[0180] The composition prepared above was introduced into a shell to manufacture a fire extinguishing assembly. The shell was manufactured in the form of an encapsulate using an outer shell in which a PET (poly (ethylene terephthalate)) film (thickness: about 10 μm), a PVDC (poly (vinylidene chloride)) film (thickness: about 40 μm) and a PP (polypropylene) film (thickness: about 50 μm) were laminated in this order. The shell was manufactured by laminating a PET film on one side of the PVDC film with an adhesive and a PP film on the other side at a temperature of about 200° C. As the PP film, a hot melt type film was used. The WVTR of the shell was about 0.11 g / m 2 · days or so. The shell is manufactured using a housing. At this time, the shell is manufactured in the form of an enclosure, specifically, in the form of a bag in a pouch-type battery cell. The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0181] Example 2

[0182] Preparation of composition

[0183] Water (tap water) (W), melamine (M), ammonium dihydrogen phosphate (N) (NH4H2PO4) (N), ammonium polyphosphate (Shifang Taifeng New Flame Retardant Co. Ltd) (A) and starch (S) are mixed in a weight ratio of 74:4.5:10:4:4.5 (W:M:N:A:S) to prepare a mixture. The solubility of ammonium polyphosphate in water at 25°C is about 40g. The same melamine, ammonium dihydrogen phosphate and starch as in Example 1 are used. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 300rpm for about 60 minutes. As starch, the starch used in Example 1 is used. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. Mixing was performed so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) was about 74:3, and the same water-absorbent polymer as used in Example 1 was applied as the water-absorbent polymer.

[0184] Manufacture of fire extinguishing assemblies

[0185] The composition was introduced into a housing to produce a fire extinguishing assembly. The housing was produced in the same form as in Example 1 using an outer shell in which a PET (poly (ethylene terephthalate)) film (thickness: about 10 μm), an aluminum foil (thickness: about 20 μm) and a PP (polypropylene) film (thickness: about 70 μm) were laminated in this order. The housing was produced by laminating a PET film on one side of the aluminum foil with an adhesive and laminating a PP film on the other side at a temperature of about 200° C. The WVTR of the housing was about 0 g / m 2 The shell is manufactured using a housing. The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0186] Example 3

[0187] Preparation of composition

[0188] Water (tap water) (W), urea (U), ammonium dihydrogen phosphate (N) (NH4H2PO4) and starch (S) are mixed in a weight ratio of 69:8.5:13:6 (W:U:N:S) to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 300rpm for about 60 minutes. As ammonium dihydrogen phosphate and starch, the same materials as in Example 1 are used. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 69:3.5, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0189] Manufacture of fire extinguishing assemblies

[0190] The composition was introduced into a shell to manufacture a fire extinguishing assembly. The shell was manufactured in the same form as in Example 1 using an outer shell in which a PET (poly(ethylene terephthalate)) film (thickness: about 10 μm), an EVOH (ethylene vinyl alcohol) film (thickness: about 40 μm) and a PE (polyethylene) film (thickness: about 50 μm) were laminated in this order. The outer shell was manufactured by laminating a PET film on one side of the EVOH film with an adhesive and laminating a PE film (hot-melt type film) on the other side at a temperature of about 200° C. The WVTR of the outer shell was about 0.27 g / m 2 The composition prepared above is introduced into a housing, and the housing is sealed to produce a fire extinguishing assembly.

[0191] Comparative Example 1.

[0192] Preparation of composition

[0193] Water (tap water) (W) and a water-absorbent polymer (SAP) (P) were mixed at a weight ratio (W:P) of 97:3 to prepare a composition. The mixing was performed at room temperature (about 25°C) under a mixing condition of 300 rpm for about 60 minutes. As the water-absorbent polymer, the same water-absorbent polymer as used in Example 1 was used.

[0194] Manufacture of fire extinguishing assemblies

[0195] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 2.

[0196] Comparative Example 2.

[0197] Preparation of composition

[0198] Water (tap water) (W), melamine (M) and ammonium dihydrogen phosphate (N) (NH4H2PO4) are mixed in a weight ratio (W:M:N) of 78:5:14 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 300rpm for about 60 minutes. The same materials as in Example 1 are used as melamine and ammonium dihydrogen phosphate. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 78:3, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0199] Manufacture of fire extinguishing assemblies

[0200] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 1.

[0201] Comparative Example 3.

[0202] Preparation of composition

[0203] Water (tap water) (W), melamine (M) and starch (S) are mixed in a weight ratio (W:M:S) of 86.5:5.5:5.5 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 300rpm for about 60 minutes. The same materials as in Example 1 are used as melamine and starch. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio (water:SAP) of water to the water-absorbent polymer (SAP) in the mixture is about 86.5:2.7, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0204] Manufacture of fire extinguishing assemblies

[0205] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 3.

[0206] Comparative Example 4.

[0207] Preparation of composition

[0208] Water (tap water) (W), melamine (M), ammonium polyphosphate (Shifang Taifeng New FlameRetardant Co. Ltd) (A) and starch (S) were mixed in a weight ratio (W:M:A:S) of 88.4:0.95:4.9:0.95 to prepare a mixture. The mixing was carried out at room temperature (about 25° C.) under a mixing condition of 500 rpm for about 10 minutes, and the same ingredients as in Example 2 were used as melamine, starch and ammonium polyphosphate. Subsequently, a composition was prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer was carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25° C.) under a mixing condition of 500 rpm for about 2 hours. The mixing was carried out so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) was about 88.4:4.8, and the same water-absorbent polymer as used in Example 1 was applied as the water-absorbent polymer.

[0209] Manufacture of fire extinguishing assemblies

[0210] The fire extinguishing assembly was manufactured by introducing the composition into the housing used in Example 2.

[0211] Comparative Example 5.

[0212] Preparation of composition

[0213] Water (tap water) (W), melamine (M), ammonium dihydrogen phosphate (N) (NH4H2PO4) and starch (S) are mixed in a weight ratio (W:M:N:S) of 45:11.3:30.9:11.3 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 500rpm for about 10 minutes. The same materials as in Example 1 are used as starch, melamine and ammonium dihydrogen phosphate (N) (NH4H2PO4). Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 45:1.5, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0214] Manufacture of fire extinguishing assemblies

[0215] The composition was introduced into a shell to manufacture a fire extinguishing assembly. The shell was manufactured using a shell in which a PVC (poly (vinyl chloride)) film (thickness: about 30 μm) and a PP (polypropylene) film (thickness: about 70 μm) were laminated in this order. The shell was manufactured by laminating a PP film on one side of the PVC film at a temperature of about 200° C. The WVTR of the shell was about 7.5 g / m 2 · days or so. The shell is manufactured using a housing. At this time, the shell is manufactured in the form of a rectangular battery cell shell (thickness of about 3 mm). The composition prepared above is introduced into the shell, and the shell is sealed to manufacture a fire extinguishing assembly.

[0216] Comparative Example 6.

[0217] Preparation of composition

[0218] Water (tap water) (W), melamine (M), magnesium carbonate (C) and starch (S) are mixed in a weight ratio (W:M:C:S) of 78:6:9.5:25 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 500rpm for about 10 minutes. The same materials as in Example 1 are used as melamine and starch. The solubility of magnesium carbonate in water at 25°C is about 0.014g. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio (water:SAP) of water to the water-absorbent polymer (SAP) in the mixture is about 78:2.5, and the same water-absorbent polymer used in Example 1 is applied as the water-absorbent polymer.

[0219] Manufacture of fire extinguishing assemblies

[0220] A fire extinguishing assembly was manufactured in the same manner as in Example 1 using the composition.

[0221] Comparative Example 7.

[0222] Preparation of composition

[0223] Water (tap water) (W), melamine (M), potassium carbonate (C) and starch (S) are mixed in a weight ratio (W:M:C:S) of 78:6:9.5:4 to prepare a mixture. The mixing is carried out at room temperature (about 25°C) under a mixing condition of 500rpm for about 10 minutes. The same materials as in Example 1 are used as melamine and starch. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is carried out by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is carried out so that the weight ratio of water to the water-absorbent polymer (SAP) in the mixture (water:SAP) is about 78:2.5, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0224] Manufacture of fire extinguishing assemblies

[0225] A fire extinguishing assembly was manufactured in the same manner as in Example 1 using the composition.

[0226] Comparative Example 8.

[0227] Preparation of composition

[0228] A silicone binder (B) (Sylgard 184), melamine (M), ammonium dihydrogen phosphate (N) (NH4H2PO4) and starch (S) are mixed in a weight ratio (B:M:N:S) of 78:6:9.5:4 to prepare a mixture. The mixing is performed at room temperature (about 25°C) under a mixing condition of 500rpm for about 10 minutes. The same materials as in Example 1 are used as melamine, ammonium dihydrogen phosphate and starch. Subsequently, a composition is prepared by further mixing a water-absorbent polymer (SAP) into the mixture. The mixing of the water-absorbent polymer is performed by mixing the mixture with the water-absorbent polymer and mixing the mixture at room temperature (about 25°C) under a mixing condition of 500rpm for about 2 hours. The mixing is performed so that the weight ratio (B:SAP) of the silicone binder (B) to the water-absorbent polymer (SAP) in the mixture is about 78:2.5, and the same water-absorbent polymer as used in Example 1 is applied as the water-absorbent polymer.

[0229] Manufacture of fire extinguishing assemblies

[0230] A fire extinguishing assembly was manufactured in the same manner as in Example 1 using the composition.

[0231] The evaluation results of the compositions and fire extinguishing assemblies of Examples and Comparative Examples are summarized in the following Tables 1 and 2. In the following Tables 1 and 2, the convection test temperature is the temperature measured with a temperature sensor after applying the flame in the above "1. Convection Test", and the unit is ° C. In the case of Comparative Examples 1, 2 and 8, melting of the aluminum pan was observed within 3 minutes, making it impossible to measure the temperature.

[0232] [Table 1]

[0233]

[0234] [Table 2]

[0235]

Claims

1. A composition comprising: Solvents; a carbonized catalyst generating agent having a solubility of 5 g or more in 100 g of water at 25° C.; and Carbonizable organic materials, wherein the composition exhibits a latent heat of 800 J / g or greater.

2. The composition according to claim 1, wherein the freezing point of the solvent is -5°C or higher.

3. The composition according to claim 1, wherein the solvent is water.

4. The composition according to claim 1, wherein the solvent is contained in an amount of 50 wt% to 95 wt%.

5. The composition according to claim 1, wherein the carbonization catalyst generating agent is phosphoric acid, a phosphoric acid compound, a phosphonate compound or a phosphate compound. 6 . The composition according to claim 1 , wherein the carbonization catalyst generating agent is included in an amount of 0.5 parts by weight to 65 parts by weight relative to 100 parts by weight of the solvent. 7 . The composition according to claim 1 , wherein the carbonizable organic material has a gelatinization viscosity of 150 BU or more.

8. The composition according to claim 1, wherein the carbonizable organic material is a polysaccharide, a polyol, cellulose, lignin, BSPPO, a carbonizable polymer or a melamine compound.

9. The composition according to claim 1, wherein the carbonizable organic material is starch comprising amylose and amylopectin. 10 . The composition according to claim 9 , wherein the starch comprises 150 to 900 parts by weight of the amylopectin relative to 100 parts by weight of the amylose. 11 . The composition according to claim 1 , wherein the carbonizable organic material is included in an amount of 0.01 parts by weight to 50 parts by weight relative to 100 parts by weight of the solvent.

12. The composition of claim 1, further comprising a gas generating material.

13. The composition of claim 12, wherein the gas generating material is one or more selected from the group consisting of melamine, guanidine, urea, melamine pyrophosphate, dicyandiamide, guanyl phosphate urea, glycine, potassium bicarbonate, sodium bicarbonate, calcium bicarbonate, magnesium bicarbonate, calcium hydroxide, magnesium hydroxide, and aluminum hydroxide. 14 . The composition according to claim 12 , wherein the gas generating material is contained in an amount of 0.01 parts by weight to 50 parts by weight relative to 100 parts by weight of the solvent.

15. A fire extinguishing assembly comprising: case; and A composition according to any one of claims 1 to 14 present in the housing.

16. A battery module, comprising: a plurality of battery cells; and A combination according to any one of claims 1 to 14 disposed between the battery cells.

17. A battery module, comprising: a plurality of battery cells; and The fire extinguishing assembly according to claim 15 is disposed between the battery cells.

Citation Information

Patent Citations

  • Modified ultrastable Y (USY) zeolite catalyst for improving low-temperature flow characteristics of distillate

    KR1020220125266A

  • Filters for fluid filtration, bypass valve devices for filters and diffuser devices for filters

    KR1020220125271A

  • Ultrasonic scanner for scanning an interior of offshore structures and ships including the same

    KR1020230041417A